KEKASARAN PERMUKAAN RESIN KOMPOSIT NANOFILLER SETELAH PENYIKATAN DENGAN PASTA GIGI WHITENING DAN NON WHITENING - Nirawati Pribadi; Cecilia G.J. Lunardhi; Aprodita Permata Y (Odonto : Dental Journal, 2017)
Background: Improving the aesthetic needs of patients is followed by various improvement and development of aesthetic dentistry products. The aesthetic demand drives the patients to choose the type of restoration which has superiority on its aesthetic properties that is nanofller composite resin. This demand also causes the patients prefer to use whitening toothpaste which its abrasive materials allegedly cause surface roughness. Surface roughness of the restoration is one of the important factors that aﬀect the durability of the restoration. High surface roughness causes the retention of plaque and dicoloration that will ultimately aﬀect the aesthetic of the restoration itself. Objective: To determine the increase of surface roughness nanofller composite resin restorations after brushing with toothpaste whitening and non-whitening.Methods: 21 samples of nanofller composite resin, divided into 3 groups. Group 1 (control) brushed with distilled water, group 2 brushed with mixture of distilled water and whitening toothpaste, and group 3 brushed using mixture of distilled water and non-whitening toothpaste. Each group was brushed with a time of 30 seconds per day for two weeks (14 days). The measurements of surface roughness were taken before and after the samples were brushed.Results: There were an increase in the surface roughness of each groupafter brushing. The result showed that the highest value of increased surface roughness occured in group 2 (whitening toothpaste), while the lowest value occured in group 1 (control). There are also signifcant diﬀerences between the value of the increased surface roughness nanofller composite resin in each group.Conclusions: The increase of surface roughness of nanofller composite resin after brushing with a whitening toothpaste was higher than brushing with non whitening toothpaste